Nursing leadership & management - Kelly, Patricia, 1941-; Kelly, Patricia (Australia : Cengage Learning Asia Pte Ltd, 2012)
This book is designed to help beginning nurses address the Institute of Medicine and The American Association of Colleges of Nursing competencies. The text prepares beginning nurse leaders and managers for modern health care. It takes in to account the Patient Protection and Affordable Care Act of 2010 and the Health Care and Education Reconciliation Act of 2010. It also reviews information from the Agency for Healthcare Quality and Research, the Joint Commission, the Leapfrog Group, Thomson Medstat, the National Quality Forum and the Institute for Healthcare Improvement, all focused on improvement of the quality and safety of patient care.[taken from the back cover].
Unit I: NURSING LEADERSHIP AND MANAGEMENT -- Unit II: LEADERSHIP AND MANAGEMENT OF THE INTERDISCIPLINARY TEAM -- Unit III: LEADERSHIP AND MANAGEMENT OF PATIENT- CENTERED CARE -- Unit V: LEADERSHIP AND MANAGEMENT OF SELF AND THE FUTURE
Includes bibliographical references and index.
Keywords: NURSING SERVICES -- ADMINISTRATION